DIPLOMASI DIGITAL KOREA SELATAN TERHADAP INDONESIAPADA MASA PANDEMI COVID-19 - Lucia Sheva Imola (2022)
ABSTRACT The era of digitalization makes all elements of the world move in accelerating the industrial revolution 4.0 where there needs to be a shift in state policies in making decisions, especially in the era of the COVID-19 pandemic. Sectors affected by the acceleration are the social, economic, political, health, defense and security sectors, tourism, etc. This study discusses how South Korea's digital diplomacy efforts towards Indonesia take advantage of the existence of science and technology to continue to carry out diplomacy in the COVID-19 era. The aim is to analyze South Korea's strategy in dealing with and tackling COVID-19 by utilizing technology and social media through the digitalization era. This study uses a descriptive qualitative method using the theory of foreign economic policy and the concept of digital diplomacy as the foundation in analyzing the diplomatic efforts carried out by South Korea in the pandemic era. The research method used is descriptive qualitative research method. The analysis of this study found that South Korea took fast steps in digital diplomacy towards Indonesia through social media such as MOFA KOREAZ, KTO.ID, KCC Indonesia, etc. The efforts made by South Korea are considered very efficient and persuasive and open new views for the Indonesian government and people to accelerate digital transformation, as for suggestions, especially for Indonesia in utilizing digital technology, namely the readiness of human resources in facing change and the role of the government in facilitating existing digital changes.